2188. A Quality Improvement Initiative for Influenza Diagnosis and Treatment within Health Systems Serving American Indian/Alaskan Native Patients. (15th December 2022) - Mera, Jorge; Montgomery, Roger; Stephens, David; Leston, Jessica; Carter, Jeffrey D; Douglas, Bonnie; Simone, Laura; Molloy, Leah
Abstract: Background: This project aimed to identify practices, knowledge and confidence in diagnosing and treating influenza in health systems serving American Indian/Alaskan Native communities and to provide education to support alignment with IDSA guidelines. Methods: Anonymous baseline surveys were completed electronically by healthcare professionals (HCPs) from Cherokee Nation Health Services (CNHS) and the Northwest Portland Area Indian Health Board's teleECHO program. Responses informed a 2-part series of live virtual educational trainings featuring pre- and post-program surveys and team-based action planning. Results: Baseline surveys were completed by 247 HCPs. 149 attended the 1 st meeting, and 90 attended the 2 nd . For outpatient influenza diagnosis, 72% of baseline survey respondents reported primarily using rapid antigen testing, and 11% reported using molecular testing. Similarly, 15% of learners in the live meetings correctly identified rapid molecular assay as the guideline-recommended test, which improved to 72% afterwards. All 9 CNHS outpatient health centers switched from rapid antigen to molecular testing for influenza diagnosis after the training. Influenza treatment decision-making was assessed using a case vignette. For a patient at high risk for complications with flu-like symptoms but stable for outpatient care, 23% of learners in the live meetings correctly chose to start antiviral treatment immediately, which improved to 54% after the program, and more learners felt confident applying diagnostic test results to treatment, from 31% before to 68% after the training. Learner confidence also improved from 19% feeling confident in selecting antiviral treatment and 33% feeling confident in identifying high risk patients before the program to 60% and 70% afterwards, respectively. Action plans prioritized by the HCPs included: patient engagement (61%), reviewing guidelines and data (57%), improving patient adherence to treatment (50%), and developing criteria for immediate antiviral treatment (50%). Conclusion: Knowledge and confidence in influenza management improved after the training, as did system-wide alignment with IDSA-recommended diagnostic testing. Studies evaluating the clinical impact of this activity is warranted. Disclosures: Jorge Mera, MD, FACP, Abbvie: Grant/Research Support|Gilead Sciences: Grant/Research Support|Gilead Sciences: Received one time honorarium for participating as a panelist in a COVID-19 Webinar|Merck: Grant/Research Support.